Evaluasi Stabilitas Lereng Menggunakan Metode Fellenius dan Software Plaxis (Studi Kasus: Ruas Jalan Simpang Kumpulan-Simpang Taman Km. 102+100, Kabupaten Agam) - Dellarosa Finnanda; Syahril Rahmat; Juniman Silalahi; Agri Americo Agamuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Road on Simpang Kumpulan–Simpang Taman section at Km. 102+100 in Agam Regency is one of the vital transportation routes in West Sumatra that frequently experiences disruptions due to landslides. This study aims to evaluate the stability of the existing slope at the location. The evaluation was carried out using two approaches: manual calculation using the Fellenius Method and numerical analysis using Plaxis 2D software. Research data were obtained from field soil testing (N-SPT) and the geometry of the existing slope. The analysis results indicate that the existing slope is in an unstable condition. The Factor of Safety (FS) of the existing slope using the manual Fellenius Method was 0.9, while the analysis using Plaxis 2D yielded 1.167. Both values are below the minimum requirement specified by SNI 8460:2017 (FS ≥ 1.5). This study also compares the results of manual calculations and numerical analysis, which show reasonably good agreement. The findings of this research are expected to provide recommendations regarding the safety level of slopes in landslide-prone areas and serve as a consideration for slope stabilization efforts in Agam Regency.